Photochemotherapy in mycosis fungoides. Issue 6097 (12th November 1977) - Hodge, L; Warin, A P; Gange, R W; Bleehen, S; Vella Briffa, D
Abstract : Six patients with mycosis fungoides were treated with methoxsalen and long-wave ultraviolet light. They were assessed clinically and histologically before and after treatment. All six patients showed clinical improvement. Histological clearing of both epidermis and dermis occurred in three patients, and epidermal clearing alone occurred in two. Photochemotherapy may have a place in the treatment of the early and intermediate stages of mycosis fungoides, and it may also be useful as an adjunct to other forms of treatment in the more advanced stages.